European earwig as a potential biological control agent of apple leafcurling midge - He, X.Z.; Wang, Q.; Xu, J. (New Zealand Plant Protection, 2008)
The European earwig Forficula auricularia L is an important predator of aphids and scales in New Zealand apple orchards To determine whether European earwig acted as a biological control agent of apple leafcurling midge (ALCM) Dasineura mali Kieffer their prey searching and feeding activity was investigated in the field and laboratory In the field in January earwigs started to leave their shelters at about 920 pm to search for ALCM larvae and returned to the shelters before 535 am with a searching peak on apple shoots infested by ALCM larvae between 1030 pm and 130 am Significantly more ALCM infested shoots and leaves were bitten by earwigs on trees where shelters trapped earwigs than on those where shelters did not trap any earwigs In the laboratory earwigs mainly fed in the first 2 hours after lightoff and each adult consumed an average of 6770 318 mature ALCM larvae during the scotophase (8 h) Heavier earwigs consumed significantly more ALCM larvae than light ones